2008
DOI: 10.1111/j.1570-7458.2008.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness and toxicity of an attracticide formulation on adult males of ash leaf cone roller, Caloptilia fraxinella

Abstract: A biodegradable attracticide formulation containing the pyrethroid insecticide permethrin and the sex pheromone of the ash leaf cone roller, Caloptilia fraxinella (Ely) (Lepidoptera: Gracillariidae), was tested for attractiveness and toxicity to males of this invasive pest of horticultural ash, Fraxinus spp. Marsh. (Oleaceae). Trap capture in attracticide-baited traps was equal to capture in traps baited with rubber septa lures releasing the known attractive pheromone. Pheromone response by male C. fraxinella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…Both in our field and laboratory investigations, there was no evidence that the 6% permethrin loading in the MalEx formulation inhibited male P. citrella response to droplets containing pheromone. These results are congruent with several other studies showing that permethrin does not repel moths in pheromone‐based attracticide formulations at loading rates ranging between 1 and 10% (Haynes et al., 1986; Evenden & McLaughlin, 2004b; Nansen & Phillips, 2004; Curkovic & Brunner, 2006; Evenden et al., 2008). At least one recent investigation of this attracticide formulation showed that the addition of permethrin did not increase efficacy against G. molesta , suggesting that mating disruption was the operative mechanism of control (Evenden & McLaughlin, 2004a).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Both in our field and laboratory investigations, there was no evidence that the 6% permethrin loading in the MalEx formulation inhibited male P. citrella response to droplets containing pheromone. These results are congruent with several other studies showing that permethrin does not repel moths in pheromone‐based attracticide formulations at loading rates ranging between 1 and 10% (Haynes et al., 1986; Evenden & McLaughlin, 2004b; Nansen & Phillips, 2004; Curkovic & Brunner, 2006; Evenden et al., 2008). At least one recent investigation of this attracticide formulation showed that the addition of permethrin did not increase efficacy against G. molesta , suggesting that mating disruption was the operative mechanism of control (Evenden & McLaughlin, 2004a).…”
Section: Discussionsupporting
confidence: 92%
“…This duration of attractiveness is lower than that observed with attracticide formulations for other moth species. An attracticide formulation targeting Epiphyas postvittana (Walker) remained highly attractive to males over a 3‐month period (Brockerhoff & Suckling, 1999), whereas another formulation targeting Caloptilia fraxinella (Ely) remained attractive for at least 5 weeks (Evenden et al., 2008). A major factor limiting the utility of MalEx as a practical control tool for management of P. citrella will be the duration it remains attractive to males in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For other gracillariid species, an attract-and-kill station and mating disruption has been investigated for Caloptilia fraxinella (Ely) in ash (Fraxinus spp.) and Phyllonorycter blancardella (F.) in orchards, respectively; so, there is an option to use a similar technology in blueberries (Trimble et al 1999, Evenden et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…To develop an integrated pest management system to monitor and control (Evenden et al 2008) this new pest of urban landscapes across the Canadian prairies, it is necessary to better understand the life history of this insect on ornamental ash plantings. In the present study, eggs, larvae, and pupae were followed during development to determine the temporal and spatial distribution of these life stages on their ash hosts.…”
Section: Introductionmentioning
confidence: 99%